2013
DOI: 10.1155/2013/246205
|View full text |Cite
|
Sign up to set email alerts
|

Role of SH Levels and Markers of Immune Response in the Stroke

Abstract: Background. Sulfhydryl groups (SH) are considered a key factor in redox sensitive reaction of plasma, and their modification could be considered an expression of abnormal generation of oxygen free radicals. Methods. Fifty consecutive patients with acute brain stroke were enclosed in this study. The plasma concentrations of SH groups were correlated to cytokines (IL-1b, IL-6, IL-8, TNF-α), plasma chitotriosidase (Chit), metalloprotease (MMP2–9), intercellular adhesion molecule-1 (ICAM-1). Results. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…This evidence suggests the overproduction of this enzyme exerts a deleterious effect in many degenerative disorders [15,[37][38][39][40]. Regarding ALS, some studies have previously shown an increased blood ChT activity suggesting this enzyme as a potential biomarker [29], and elevated ChT levels in ALS-CSF proposing a role for the enzyme in the disease pathogenesis [16,18]. Chitin, the natural substrate of ChT in unvertebrates animals, is an insoluble N-acetylglucosamine polymer and it is uncertain whether ChT activity in CSF reflects only a microglia activation or if some chitin-like polysaccharides at CNS could be the substrate of this enzyme [17].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This evidence suggests the overproduction of this enzyme exerts a deleterious effect in many degenerative disorders [15,[37][38][39][40]. Regarding ALS, some studies have previously shown an increased blood ChT activity suggesting this enzyme as a potential biomarker [29], and elevated ChT levels in ALS-CSF proposing a role for the enzyme in the disease pathogenesis [16,18]. Chitin, the natural substrate of ChT in unvertebrates animals, is an insoluble N-acetylglucosamine polymer and it is uncertain whether ChT activity in CSF reflects only a microglia activation or if some chitin-like polysaccharides at CNS could be the substrate of this enzyme [17].…”
Section: Discussionmentioning
confidence: 91%
“…In human brain, it is suggested that ChT is synthesized by microglia [16] and it has been reported that high CSF ChT levels in several neurological conditions including multiple sclerosis, acute ischemic stroke, and Alzheimer's disease (AD) [12][13][14][15]36]. This evidence suggests the overproduction of this enzyme exerts a deleterious effect in many degenerative disorders [15,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experimental study on the effects of artery ballooning and oxidative stress on the injury of vascular smooth muscle cells revealed decrease in blood glutathione concentration after the procedure [32]. In humans, plasma sulfhydryl groups concentrations decreased within 24 hours after ischemic stroke onset and correlated positively with interleukin-8 and negatively with chitotriosidase (a marker of macrophage activation) and matrix metalloprotease 2 [18]. The latter study shows that plasma sulfhydryl groups concentration can be modified by acute inflammatory/immune response; thus it can be the case after CAS.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins, albumins especially, are the principal source of SG in plasma [17]. The concentration of plasma sulfhydryl groups decreases during acute cerebral ischemia and correlates with immune response in stroke patients [18]. …”
Section: Introductionmentioning
confidence: 99%